Investigation of microstructural and magnetic properties of Ca2+ doped strontium hexaferrite nanoparticles - Sachin Kumar Godara; Mankamal Preet Kaur; Varinder Kaur; Parambir Singh Malhi; Mandeep Singh; Swati Verma; Rohit Jasrotia; Jahangeer Ahmed; Mohaseen S. Tamboli; Ashwani Kumar Sood (Journal of King Saud University: Science, 2022)
The effect of Ca2+ ions doping on the structure, magnetic properties, and surface morphology of Sr1-xCaxFe12O19 (x = 0.0 to 0.5 with step size 0.1) hexaferrite nanoparticles synthesized using the sol–gel auto-combustion technique was investigated in the current study. The phase purity of synthesized samples is confirmed by XRD data plots up to x = 0.2, after which α-Fe2O3 was observed as a secondary phase in all concentrations. The micrographs from FESEM show that with the increase in the concentration of Ca2+ dopant, the average grain size increases from ≈125 nm to ≈240 nm. The intensity of secondary phase Raman peaks increases with increasing dopant ion concentration beyond x = 0.2. The coercivity value varies between 5292 and 5828 Oe as the Ca2+ dopant increases. A maximum (72.63 emu/g) value of saturation magnetization (Ms) have been obtained in samples at x = 0.2. Such substances can be utilized for making permanent magnets applications.